2021
DOI: 10.3390/ijms222212456
|View full text |Cite
|
Sign up to set email alerts
|

Significance of GABAA Receptor for Cognitive Function and Hippocampal Pathology

Abstract: The hippocampus is a primary area for contextual memory, known to process spatiotemporal information within a specific episode. Long-term strengthening of glutamatergic transmission is a mechanism of contextual learning in the dorsal cornu ammonis 1 (CA1) area of the hippocampus. CA1-specific immobilization or blockade of α-amino-3-hydroxyl-5-methyl-4-isoxazole-propionate (AMPA) receptor delivery can impair learning performance, indicating a causal relationship between learning and receptor delivery into the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 120 publications
(172 reference statements)
1
16
0
Order By: Relevance
“…In the present investigation, we found that hCMEC/D3 cells express the following GABA A receptor subunits: α1 (also confirmed by immunoblotting), α5, β1, β2, and γ1. Therefore, human cerebrovascular endothelial cells possess all the three distinct GABA A receptor subunits that can arrange into a pentameric ion channel with the likely stoichiometry 2α:2β:1γ [ 3 , 6 ]. Based upon their expression levels, GABA A receptors in hCMEC/D3 cells are predicted to incorporate the α1, β1, and γ1 subunits.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present investigation, we found that hCMEC/D3 cells express the following GABA A receptor subunits: α1 (also confirmed by immunoblotting), α5, β1, β2, and γ1. Therefore, human cerebrovascular endothelial cells possess all the three distinct GABA A receptor subunits that can arrange into a pentameric ion channel with the likely stoichiometry 2α:2β:1γ [ 3 , 6 ]. Based upon their expression levels, GABA A receptors in hCMEC/D3 cells are predicted to incorporate the α1, β1, and γ1 subunits.…”
Section: Discussionmentioning
confidence: 99%
“…The neurotransmitter γ-aminobutyric acid (GABA) is not only crucial to maintain a proper excitatory:inhibitory balance in neuronal networks by inhibiting glutamatergic pyramidal neurons [ 1 , 2 , 3 ], but is also instrumental to generate synchronized network oscillations that underpin optimal cognitive functions [ 4 , 5 ]. GABA dampens neuronal excitability by gating Cl − -permeable GABA A receptors, thereby enabling Cl − influx down the electrochemical gradient and hyperpolarizing the membrane potential [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…GABAergic dysfunction has gained increasing attention in recent years. In this respect, a significant reduction in GABA concentration in the temporal lobe, selective reduction of GABAergic inhibitory interneurons and a reduction of GABAergic terminals, especially in the areas closest to amyloid plaques, have all been reported in animal models [23,85,93,94]. This decreased GABAergic tone [12] leads to abnormal cortical hypersynchronization and could also decrease neuro and synaptogenesis [93,94].…”
Section: Role Of Neurotransmitters In Epiletogenesismentioning
confidence: 91%
“…In experimental animal models, GABA receptor hyperactivation inhibits the release of glutamate and dopamine, thereby reducing the levels of other neurotransmitters linked to behavior modulation through its ability to regulate cognitive function. Further, studies showed that alterations in the expression of GABA receptors in animals impairs memory function [ 102 , 103 ], and prenatal alcohol exposure can chronically alter brain development and function in the offspring [ 104 ]. One study on cortical plate samples from fetal and infant brains demonstrated insufficient and delayed production of GABAergic interneurons in the ganglion during the two first trimesters of pregnancy and their delayed incorporation into the laminar structures of the frontal cortex, as well as mispositioning of GABAergic and calretininergic interneurons throughout fetal life [ 105 ].…”
Section: Activation Of the Gaba Receptor In The Cns Of The Fetus In R...mentioning
confidence: 99%